Analysis Of Financial Distress With Profitability As Moderation Variable - Wiwi Idawati; Aditya Kusuma Wardhana (Jurnal Akuntansi, 2021)
The purpose of this research is to know and analyze the performance of profitability to measure its ability to strengthen or weaken about impact liquidity, leverage, and also operating capacity for financial distress. Furthermore, there are 39 of Indonesia Stock Exchange infrastructure companies as long as 2016-2020 as samples in this study. The results of the data analysis show that liquidity variables do not signiifkan to financial distress, and leverage is significantly positive to financial distress and operating capacity is significantly negative to financial distress. Profitability strengthens liquidity relationships to financial distress. As for the relationship of leverage and also operating capacity to financial distress can not be moderated profitability.